RETENTION OF TALENT IN THE PUBLIC SERVICE (PRÁXIS EM SAÚDE, 2025)
Retaining talent is one of the main challenges faced by the Brazilian federal public service. This is largely due to its rigid structure and the limitations imposed by legislation. This study sought to evaluate this issue, emphasizing the strategic role of the public service in the country’s development, its structural particularities, and the factors that make it difficult to retain talented employees. Key concepts were analyzed, such as providing conditions for professional development and creating a positive work environment. Ideas to reduce the turnover of professionals were also discussed, including the reformulation of career plans, continuous training, recognition and appreciation, as well as flexible work systems.
Keywords: Talent Retention; Federal Public Service; Human Resource Management